INDONESIAN AND PACIFIC ISLAND PALAEOECOLOGY GAUGING THE IMPACT OF PREHISTORIC SETTLEMENT - Joshua Griffin (BRIN, 2011)
Anthropogenic optimal foraging models have provided a theoretical foundation for evaluating fluctuations in human resource use, thereby providing archaeology with a platform to present various theories on prehistoric island resource exploitation and habitat alteration. This paper cross-examines three major elements of remains found in island assemblages: those being avifauna, marine fauna, and palaeobotanical remains (from Henderson Island, American Samoa and Hawaii, and eastern Indonesia respectively). In doing so, the sequence of prehistoric resource depression or extinction should be readily identified through this anthropogenic behaviour. However, the Polynesian faunal assemblages shed more light on anthropogenic impact than the palaeobotanical record from Indonesia. Nevertheless, as a comparative study, this information provides a framework for present-day management and the potential restoration of these island ecosystems.